PENGARUH KOMBINASI TEPUNG BEKATUL DAN TEPUNG MENIR C4 TERHADAP BEBERAPA KOMPONEN MUTU COOKIES - Mira Idora; Agustono Prarudiyanto; Ahmad Alamsyah (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2017)
The purpose of this research was to know the best combination of rice bran and grains of rice flour that cloud be seen from some quality components of cookies include moisture, protein and ash content, organoleptic quality such as flavour referring to National Indonesian Standard (SNI). This research use Compoletely Randomized Block Design, consist of six treatments (100% wheat flour, 30% rice bran: 70% grains of rice flour, 40% rice bran: 60% grains of rice flour, 50% rice bran: 50% grains of rice flour, 60% rice bran: 40% grains of rice flour, 70% rice bran: 30% grains of rice flour) with three replications. The data were analyzed using Analysis of Variance diversity at 5% significance level using Co-Stat Software and tested further using Orthogonal Polynomials test if there was real difference. The results showed that the proportion of rice bran and grain of rice flour had significant effect on taste, aroma, texture and color (hedonic and scoring), protein and ash content, but not significantly different to moisture of cookies. The results of this study also showed that the proportion of white rice brain and grains of rice flour which produced cookies with the best quality in accordance with SNI quality requirements was the treatment of 30% rice bran: 70% grains of rice flour (4.8008% moisture, 6.0461% protein content and 1.9274% ash content, with flavor, aroma, texture and color which was very favored by the panelists where cookies with yellowish brown color and slightly crunchy texture). Keywords:cookies, grains of rice flour, rice bran flour, white rice. ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui kombinasi terbaik dari tepung bekatul dan tepung menirterbaik dilihat dari beberapa komponen mutu cookies meliputi kadarair, kadar protein, kadar abu dan mutu organoleptik seperti bau, rasa, aroma dan tekstur yang mengacu pada Standar Nasional Indonesia (SNI). Penelitian ini menggunakan Rancangan Acak Kelompok (RAK), terdiri dari enam perlakuan (Tepung terigu 100%, Tepung Bekatul 30%: Tepung Menir 70%, Tepung Bekatul 40% : Tepung Menir 60%, Tepung Bekatul 50% : Tepung Menir 50%, Tepung Bekatul 60% : Tepung Menir 40% dan Tepung Bekatul 70%: Tepung Menir 30%) dengan tiga kali ulangan. Data hasil penelitian dianalisis menggunakan analisis keragaman ANOVA (Analysis of Variance) pada taraf 5% menggunakan Software Co-Stat dan diuji lanjut menggunakan uji lanjut Polinomial Ortogonal jika terdapat beda nyata. Hasil penelitian menunjukkan bahwa proporsi tepung bekatul dan tepung menir memberikan pengaruh yang berbeda nyata terhadap parameter rasa, aroma, tektur dan warna (Hedonic dan Scoring), kadar protein dan kadar abu, namun tidak berbeda nyata terhadap kadar air cookies. Hasil penelitian ini juga menunjukkan bahwa proporsi tepung bekatul dan tepung menir yang menghasilkan cookies dengan mutu terbaik yang sesuai dengan syarat mutu SNI adalah perlakuan tepung bekatul 30% : tepung menir 70% (kadar air 4,8008%, kadar protein 6,0461% dan kadar abu 1,9274%, dengan rasa, aroma, tektur dan warna sangat disukai panelis dimana cookies berwarnacokelat kekuningan dan tekstur agak renyah). Kata kunci:beras putih, cookies, tepung bekatul, tepung menir